Strategi Penyiaran Dakwah Islam Berbasis Media Penyiaran Digital - Wahyudi, Ryan; Tasruddin, Ramsiah (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
In the current digital era, technological advancements are progressingrapidly and offer significant opportunities for preachers to disseminatetheir messages. The purpose of this article is to analyze strategies fordelivering Islamic da'wah through digital media. These strategiesinclude first, da'wah through graphic design; second, da'w ah throughwebsites; and third, da'wah through podcasts. Additionally, this articleaddresses the opportunities and challenges of da'wah in the digital age,including political factors, emotional support, spiritual intelligence, andthe importance of mental health from a religious perspective. Theresearch method employed in this article is library research. This workaims to assist preachers in continuously innovating their methods ofcommunication, ensuring they remain relevant in an increasinglysophisticated modern world.